Neuroplasticity and aphasia treatments: new approaches for an old problem. Issue 10 (4th May 2019) - Crosson, Bruce; Rodriguez, Amy D; Copland, David; Fridriksson, Julius; Krishnamurthy, Lisa C; Meinzer, Marcus; Raymer, Anastasia M; Krishnamurthy, Venkatagiri; Leff, Alexander P
Abstract : Given the profound impact of language impairment after stroke (aphasia), neuroplasticity research is garnering considerable attention as means for eventually improving aphasia treatments and how they are delivered. Functional and structural neuroimaging studies indicate that aphasia treatments can recruit both residual and new neural mechanisms to improve language function and that neuroimaging modalities may hold promise in predicting treatment outcome. In relatively small clinical trials, both non-invasive brain stimulation and behavioural manipulations targeting activation or suppression of specific cortices can improve aphasia treatment outcomes. Recent language interventions that employ principles consistent with inducing neuroplasticity also are showing improved performance for both trained and novel items and contexts. While knowledge is rapidly accumulating, larger trials emphasising how to select optimal paradigms for individualised aphasia treatment are needed. Finally, a model of how to incorporate the growing knowledge into clinical practice could help to focus future research.